Фізико-механічні властивості низькоемісійних багатокомпонентних цементів - Іващишин, Г. С.; Ivashchyshyn, H. (Видавництво Львівської політехніки, 2018)
Виробництво композиційних цементів відповідно до ДСТУ Б EN 197-1:2015 надає можливості скорочення вмісту портландцементного клінкеру до 20–64 %, що відповідає концепції сталого розвитку. Використання цементозаміщувальних матеріалів у виробництві цементу та бетону створює широкі можливості розроблення ефективних низькоемісійних багатокомпонентних цементів з пониженим “клінкер-фактором”. Досліджено фізико-механічні властивості низькоемісійних багатокомпонентних цементів СЕМ V/A із вмістом доменного гранульованого шлаку як складника гідравлічної дії, цеоліту як добавки пуцоланової дії і вапняку – мікронаповнювача. Показано, що завдяки синергетичному поєднанню цих складників досягається клас міцності композиційних цементів СЕМ V/А 32,5 із зменшенням вмісту клінкерної складової до 50 %.

One of the main tasks of building industry is to reduce carbon dioxide emissions, which are generated during the cement production, without losing the properties and quality of the binding agent. Production of composite cements according to DSTU B EN 197-1: 2015, which describes the principles of classification and requirements for common cements of general construction purposes, creates prospects for improving the efficiency of cement production due to the possibility of reducing the content of Portlandcement clinker and increasing the amount of supplementary cementitious materials (SCMs), which corresponds to Concepts of Sustainable Development. The use of supplementary cementitious materials in the cement production creates wide opportunities for the development of efficient low-energy blended cements with a reduced “clinker factor”. Physical and mechanical properties of low-emission quarterly composite cements CEM V/A with the content of blast furnace granulated slag as a component of hydraulic action, zeolite as supplements of pozzolan and limestone as a microfiller are investigated in this article. It is shown that Strength class Compressive strength is obtained for composite cements CEM V/A – 32.5 with the decrease clinker-faktor up to 50 % due to the synergistic combination of SCMs. Composite cement CEM V / A 32.5 R with supplementary cementitious materials content 50 % by weight is characterized by a 1.75 times higher specific surface than CEM I 42.5 R. while the value of standard consistency of cements paste is close to CEM I 42.5 R. For CEM V/A 32.5 R the initial setting time is 180 min and final – 282 min.
Mechanical and physical properties of low-energy multicomponent cements
Keywords: низькоемісійний багатокомпонентний цемент; цементозаміщувальні матеріали; емісія СО2; клінкер-фактор; міцність при стиску; low-energy multicomponent cements; supplementary cementitious materials; CO2 emissions; clinker-faktor; Strength class Compressive strength; 666.945